2006
DOI: 10.2460/javma.229.12.1949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rate of development of septic arthritis after elective arthroscopy in horses: 7 cases (1994–2003)

Abstract: Results can be used for comparison with data from other institutions and surgical facilities. Additional precautions should be undertaken when arthroscopic surgery involves draft breeds and tibiotarsal joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
53
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 14 publications
9
53
0
2
Order By: Relevance
“…There are no standard guidelines for perioperative prophylaxis in horses or data that indicate a requirement for perioperative prophylaxis for arthroscopy. While this study was not designed to assess the efficacy of perioperative prophylaxis, the 0.67% SSI rate is comparable to previously reported rates of 0.14%–1.5% and the 0% rate reported in the previous study at this institution . Care must be taken when comparing studies; however, it is important to note that a study reporting a 0.7% infection rate after arthroscopy involved 444 horses, none of which received any antimicrobials .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are no standard guidelines for perioperative prophylaxis in horses or data that indicate a requirement for perioperative prophylaxis for arthroscopy. While this study was not designed to assess the efficacy of perioperative prophylaxis, the 0.67% SSI rate is comparable to previously reported rates of 0.14%–1.5% and the 0% rate reported in the previous study at this institution . Care must be taken when comparing studies; however, it is important to note that a study reporting a 0.7% infection rate after arthroscopy involved 444 horses, none of which received any antimicrobials .…”
Section: Discussionsupporting
confidence: 82%
“…Care must be taken when comparing studies; however, it is important to note that a study reporting a 0.7% infection rate after arthroscopy involved 444 horses, none of which received any antimicrobials . Furthermore, two studies with mixed populations of horses treated or not treated with antimicrobials identified no association of antimicrobial prophylaxis with SSI rate after arthroscopy or a broader category of orthopedic surgery . While randomized clinical trials evaluating the impact of antimicrobial prophylaxis on SSI after arthroscopy are lacking in horses, current data do not support a requirement for antimicrobials for elective arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, systemic antimicrobial therapy was continued up to a maximum of 48 h following surgery and if synovial contamination occurred at the time of surgery, clinical signs of synovial sepsis would be anticipated to develop 3–4 days post operatively. Hence, the prolonged time period in this study and others , suggest that synovial infection developed post operatively and not at the time of surgery.…”
Section: Discussionsupporting
confidence: 53%
“…This was implicated as the reason why tarsocrural joints were at increased risk of developing synovial sepsis following arthroscopy by Olds et al . .…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of procedures would need to be examined to explore this relationship further. Interestingly, studies on equine surgery showed no difference in SSI when antibiotics were or were not used, and were all minimally invasive surgeries . Minimally invasive procedures in our study were associated with fewer glove perforations.…”
Section: Discussionmentioning
confidence: 45%